Profile of patients with genitourinary anomalies treated in a clinical genetics service in the Brazilian unified health system - Ilanna Fragoso Peixoto Gazzaneo; Camila Maia Costa de Queiroz; Larissa Clara Vieira Goes; Victor José Correia Lessa; Reinaldo Luna de Omena Filho; Diogo Lucas Lima do Nascimento; Reginaldo José Petroli; Susane Vasconcelos Zanotti; Isabella Lopes Monlleó (Sociedade de Pediatria de São Paulo, 2016)
Abstract Objective: To describe the profile of patients with genitourinary abnormalities treated at a tertiary hospital genetics service. Methods: Cross-sectional study of 1068 medical records of patients treated between April/2008 and August/2014. A total of 115 cases suggestive of genitourinary anomalies were selected, regardless of age. A standardized clinical protocol was used, as well as karyotype, hormone levels and genitourinary ultrasound for basic evaluation. Laparoscopy, gonadal biopsy and molecular studies were performed in specific cases. Patients with genitourinary malformations were classified as genitourinary anomalies (GUA), whereas the others, as Disorders of Sex Differentiation (DSD). Chi-square, Fisher and Kruskal-Wallis tests were used for statistical analysis and comparison between groups. Results: 80 subjects met the inclusion criteria, 91% with DSD and 9% with isolated/syndromic GUA. The age was younger in the GUA group (p<0.02), but these groups did not differ regarding external and internal genitalia, as well as karyotype. Karyotype 46,XY was verified in 55% and chromosomal aberrations in 17.5% of cases. Ambiguous genitalia occurred in 45%, predominantly in 46,XX patients (p<0.006). Disorders of Gonadal Differentiation accounted for 25% and congenital adrenal hyperplasia, for 17.5% of the sample. Consanguinity occurred in 16%, recurrence in 12%, lack of birth certificate in 20% and interrupted follow-up in 31% of cases. Conclusions: Patients with DSD predominated. Ambiguous genitalia and abnormal sexual differentiation were more frequent among infants and prepubertal individuals. Congenital adrenal hyperplasia was the most prevalent nosology. Younger patients were more common in the GUA group. Abandonment and lower frequency of birth certificate occurred in patients with ambiguous or malformed genitalia. These characteristics corroborate the literature and show the biopsychosocial impact of genitourinary anomalies.